The Department of Continuing Professional Development (CPD) of BCPS - Ensuring the Proficiency & Competency of Health Professionals (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Abstract not availableJ Bangladesh Coll Phys Surg 2022; 40: 116-117